A prospective study of radionuclide biliary scanning in acute pancreatitis. - Neoptolemos, J. P. (Royal College of Surgeons of England, 1983)
Early surgery for biliary pancreatitis has resulted in a need for an accurate method of gallstone detection in acute pancreatitis. Fifty patients with acute pancreatitis were studied prospectively to assess the diagnostic value of Radionuclide Biliary Scanning (RBS) performed within 72 hours of an attack. To assess the general accuracy of RBS a further 154 patients with suspected acute cholecystitis or biliary colic were similarly studied. There were 34 patients with biliary pancreatitis and 18 (53%) had a positive scan (no gallbladder seen). There were 16 patients with non-biliary pancreatitis and 5 (31%) had a positive scan. All 51 patients with acute cholecystitis had a positive scan, as did 82% of the 51 patients with biliary colic. There were 52 patients with no biliary or pancreatic disease and none of these had a positive scan. RBS is highly accurate in confirming a diagnosis of acute cholecystitis or biliary colic. However, it cannot be relied on to differentiate between biliary and non-biliary pancreatitis and should certainly not be used as the basis for biliary surgery in these patients.